Assessing socio-cultural factors affecting integration of Almajiris into formal education system in Katsina state, Nigeria - Adekunle Thomas Olutola; Rafiu Ademola Olatoye; Garba Kofanaisa Adamu (Intelektual Pustaka Media Utama, 2021)
This study investigated the socio-cultural factors affecting integration into the formal education system in Katsina State, Nigeria. Descriptive survey design was adopted for this study. There were 653 Almajiris purposively selected from twelve Almajiris schools in Katsina State. A researcher-designed questionnaire titled: ‘‘Almajiris socio-cultural factors questionnaire’’ (ASCFQ) with test-retest reliability coefficient of 0.88 was used to collect data for the study. Analysis of data was carried out using frequencies and percentages. Findings revealed that most parents abandon their children in these informal Arabic schools. Most Almajiris (603, that is 92.3%) responded that their Mallams (Teachers) do not feed them. Therefore, the only means of survival is through begging and doing menial jobs. Based on these findings, it is recommended that all the identified socio-economic factors affecting the integration of Almajiris into the formal education system should be addressed by the government. This can be done through public enlightenment campaigns and provision of incentives.